2006
DOI: 10.1007/s10529-005-5718-6
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid-3′,5′-hydroxylase from Phalaenopsis: A Novel Member of Cytochrome P450s, its cDNA Cloning, Endogenous Expression and Molecular Modeling

Abstract: A novel cDNA for the flavonoid-3',5'-hydroxylase (F35H) gene was cloned from petals of Phalaenopsis, and designated as Phf35h (accession number DQ148458 in GenBank/EMBL/DDBJ). The genomic clone of Phf35h was isolated by a PCR-based strategy. Nucleotide sequence analysis revealed that its genomic clone contains one intron and an open reading frame encoding a polypeptide of 507 amino acid residues. Southern hybridization analysis indicated the presence of a single gene coding for Phf35h. RT-PCR analysis showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…The unknown-function CYP76C1 gene was highly expressed in the flowers of A. thaliana, and at lower level in the leaves (Mizutani et al 1998). The expression pattern of CYP76AB1 we describe here in the petals of V. coerulea is similar to the expression patterns of F3'5'H in the petals of Eustoma grandiflorum (Nielsen and Podivinsky 1997), Nierembergia (Yukiko et al 2006) and Phalaenopsis (Wang et al 2006). In Vinca major, although the transcripts of the F3'5'H gene were detected in all five developmental stages of the flower, strong signals were only detected in the petals of flowers in stages 2 -4 ( Mori et al 2004).…”
supporting
confidence: 78%
“…The unknown-function CYP76C1 gene was highly expressed in the flowers of A. thaliana, and at lower level in the leaves (Mizutani et al 1998). The expression pattern of CYP76AB1 we describe here in the petals of V. coerulea is similar to the expression patterns of F3'5'H in the petals of Eustoma grandiflorum (Nielsen and Podivinsky 1997), Nierembergia (Yukiko et al 2006) and Phalaenopsis (Wang et al 2006). In Vinca major, although the transcripts of the F3'5'H gene were detected in all five developmental stages of the flower, strong signals were only detected in the petals of flowers in stages 2 -4 ( Mori et al 2004).…”
supporting
confidence: 78%
“…The Lasergene program MegAlign (DNASTAR Inc., Madison, USA) was used to compare the CpF3'5'H deduced amino acid sequence with ten F3'5'H sequences (the CYP75A group), ten F3'H sequences (CYP75B) and two 'outlier' cytochrome P450 sequences (data not shown). Amino acid identity of CpF3'5'H to other F3'5'H sequences was in the range from 75-82%, except for the Campanula medium F3'5'H sequence (BAA03440), 68% identity, which is suggested to have a distinct F3'5'H structure [16] and the monocot Phalaenopsis hybrida F3'5'H sequence (AAZ79451, 50% identity) [17]. A phylogenetic tree was formed using the CLUSTAL W algorithm http://www-bimas.cit.nih.gov/clustalw/clustalw.html with the MegAlign data (Figure.…”
Section: Resultsmentioning
confidence: 99%
“…The expression level of the F3 ′ 5 ′ H homolog in Torenia hybrida was higher during the early period than the late period (Ueyama et al ); however, the opposite expression pattern exists in Gentiana triflora (Nakatsuka et al ). Although F3 ′ 5 ′ H was highly expressed during the late period, its expression was not detected during the early period in Eustoma grandiflorum , Phalaenopsis and V. vinifera (Noda et al , Bogs et al , Wang et al ). Thus, the expression pattern of cineraria F3 ′ 5 ′ H during floral development is specific.…”
Section: Discussionmentioning
confidence: 99%
“…Only ligulate florets of purple and blue cineraria contain delphinidin derivatives (Sun et al ); consequently, the difference in PCFH expression during the primary period is a likely reason for the production of diverse anthocyanidins to form various colors. Except in the berry skin of V. vinifera (Bogs et al ), the transcripts of F3 ′ 5 ′ H were detected only in the floral organs of T. hybrida , E. grandiflorum , G. triflora , Phalaenopsis and Solanum lycopersicum (Ueyama et al , Noda et al , Nakatsuka et al , Wang et al , Olsen et al ). This study found for the first time that F3 ′ 5 ′ H is expressed in cineraria leaves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation